Sex Hormones Protect Against Amyloid‐β Induced Oxidative Stress in the Choroid Plexus Cell Line Z310. (19th August 2016) - Costa, A. R.; Marcelino, H.; Gonçalves, I.; Quintela, T.; Tomás, J.; Duarte, A. C.; Fonseca, A. M.; Santos, C. R. A.
Abstract : The choroid plexus (CP) epithelium is a unique structure in the brain that forms an interface between the peripheral blood on the basal side and the cerebrospinal fluid (CSF) on the apical side. It is a relevant source of many polypeptides secreted to the CSF with neuroprotective functions and also participates in the elimination and detoxification of brain metabolites, such as β‐amyloid (Aβ) removal from the CSF through transporter‐mediated influx. The CP is also a target tissue for sex hormones (SHs) that have recognised neuroprotective effects against a variety of insults, including Aβ toxicity and oxidative stress in the central nervous system. The present study aimed to understand how SHs modulate Aβ‐induced oxidative stress in a CP cell line (Z310 cell line) by analysing the effects of Aβ1–42 on oxidative stress, mitochondrial function and apoptosis, as well as by assessing how 17β‐oestradiol (E2 ) and 5α‐dihydrotestosterone (DHT) modulated these effects and the cellular uptake of Aβ1–42 by CP cells. Our findings show that E2 and DHT treatment reduce Aβ1–42 ‐induced oxidative stress and the internalisation of Aβ1–42 by CP epithelial cells, highlighting the importance of considering the background of SHs and therefore sex‐related differences in Aβ metabolism and clearance by CP cells.